Prognostic value of molecular subtypes and other factors on disease-free survival in women with breast cancer at Universiti Sains Malaysia Hospital - Wei, Oh Chen (2018)
Introduction: Breast cancer is the most common cancer in Malaysia with a 5-year incidence of 18,206 patients during 2007-2011. Approximately 2,572 patients died of breast cancer in 2012 in Malaysia. Objective: The study assessed the five-year disease-free survival (5-y DFS), distribution of molecular subtypes and other prognostic factors of breast cancer. Methods: A single-center retrospective review was conducted on 208 patients with non-metastatic, operable breast cancer treated with mastectomy or breast-conserving surgery between 2007 and 2015. Data collected included patients’ demographics, tumour’s characteristics, histopathological profiles, receptor status and treatment modalities. Molecular subtypes of breast cancer were subdivided into four groups: Luminal A: ER+ and/or PR+ and HER2- Luminal B: ER+ and/or PR+ and HER2+; HER-2 enriched: ER-, PR- and HER2+; Triple negative: ER-, PR- and HER2-. Ratio of positive lymph nodes (LNs) and dissected LNs was classified as 0, ≤0.20, >0.20 and ≤ 0.65 and > 0.65. Kaplan-Meier survival analysis was performed. Cox proportional hazards regression was used to determine prognosis factor. Result: The distribution of molecular subtypes among 208 patients was: Luminal A (35.2%), Luminal B (29.0%), HER2-enriched (18.1%), and Triple-negative (17.6%). In univariable analysis, the molecular subtype was not associated with DFS. However, both absolute number of positive lymph nodes and the LNR were significant prognostic factors of DFS. In multivariable analysis, the positive LNs lost significance and the LNR remained as a prognostic factor of DFS, patients had increased risk (aHR: 1.17; 95% CI: 1.10 - 1.26) to experience any recurrence or death for every increasing of 0.1 unit in LNR when radiotherapy was adjusted for. Conclusion: The present study reported the Luminal type breast cancer was the most common subtype of breast cancer among female patients. The study also demonstrates that LNR is a better prognostic factor in predicting DFS than the absolute number of positive LNs. Molecular subtype is not a significant prognostic factor.